Antibiotic Resistance and Food Safety: Perspectives on New Technologies and Molecules for Microbial Control in the Food Industry - Wu Wu, Jannette Wen Fang (2023)
Antibiotic resistance (ABR) has direct and indirect repercussions on public health and threatens to decrease the therapeutic effect of antibiotic treatments and lead to more infection-re-lated deaths. There are several mechanisms by which ABR can be transferred from one microorgan-ism to another. The risk of transfer is often related to environmental factors. The food supply chain offers conditions where ABR gene transfer can occur by multiple pathways, which generates con-cerns regarding food safety. This work reviews mechanisms involved in ABR gene transfer, poten-tial transmission routes in the food supply chain, the prevalence of antibiotic residues in food and ABR organisms in processing lines and final products, and implications for public health. Finally, the paper will elaborate on the application of antimicrobial peptides as new alternatives to antibiot-ics that might countermeasure ABR and is compatible with current food trends.